Evaluation of heart and aortic injuries in autopsy cases - Turkoglu, Abdurrahim; Bork, Turgay; Tokdemir, Mehmet; Ustunel, Latif (Romanian Legal Med Soc, 2018)
Studies conducted with autopsy series provide essential contributions in determining injury mechanisms in many types of trauma. The aim was to contribute to the improvement of new preventive measures by revealing the factors and injury mechanisms that play a role in the present of heart and aortic injuries. 126 patients were included in the study for 5 years. It was observed that the most common injury was caused by traffic accidents (39.7%, injury inside the vehicle). Heart injury was observed in 63.4% of the cases. The aortic injury occurred in 57.9% of cases. heart and aortic injuries should be associated with the case of thorax trauma. Accordingly, the necessary clinical approach should be made, the use of safety belts should be ensured in the vehicles, and new measures should be developed to prevent people from being thrown away in the vehicle during an accident.
Keywords: forensic science; trauma; injury; aorta; death; thoracic injuries